Complete mitochondrial genome of Cheilio inermis (Labriformes, Labridae). Issue 2 (3rd July 2018) - Song, Ha Yeun; Jo, Seonmi; Jung, Seung-Hyun; Hwang, Hyun-Ju; An, Hye Suck
Abstract: In the present report, we describe the first sequencing and assembly of the complete mitochondrial genome of Cheilio inermis . The mitochondrial genome of C . inermis, with 16, 494 bp in length, has the typical vertebrate mitochondrial gene arrangement. It contains 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and a control region. All the tRNA genes typically formed a cloverleaf secondary structure. Phylogenetic analysis using mitochondrial genomes of 11 species showed that C. inermis formed monophyletic group with other Labridae species.